DAMPAK PERUBAHAN BUDAYA KOTA BAU BAU TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; Rachel Maryam; Annisa (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the significant impact of cultural changes occurring in Baubau City on the learning process at the elementary school level. As the urban center and former seat of the Buton Sultanate, Baubau City faces a critical shift in local wisdom values. The primary issue addressed is the erosion of the tradition of politeness (poma-maa-maa) and the declining use of the Wolio regional language, both of which are being marginalized by modernization and the intensive use of digital technology by students. This research employs a descriptive qualitative method, utilizing participatory observation, in-depth interviews with educators, and an analysis of local content curriculum documents. The findings indicate that cultural transformation significantly impacts the decline of discipline based on local values and reduces students' understanding of their cultural identity as heirs to the Sultanate's legacy. Conversely, these changes present opportunities for integrating dynamic digital-based learning media. In conclusion, there is an urgent need to reconstruct the local content curriculum to harmonize technological advancement with the preservation of noble Butonian values, ensuring the progressive development of educational theory and practice in Baubau City.